The Political Discourse on Croatia’s EU Accession: a Rhetorical Analysis of the Presentation of the European Union among Supporters and Opponents of the EU - Kišiček, Gabrijela (Array, 2013)
his article describes salient argumentation strategies used in speeches of members of the political majority in support of Croatian EU membership as well as and those who opposed it. The analysis includes the usage of ideologically marked words, expressive terms with emotional value, and figures of speech, particularly metaphor. Corpora for this research were political speeches broadcast on television and radio collected over a period of 3 months, including the most important political figures of the previous and the present government as well as representatives of “Europhobes,” such as leaders of right wing political parties and civil organizations. The main goal of the analysis is to determine what kinds of arguments are frequently used, which fallacies are most frequent, and what are the differences and similarities in rhetorical means and argumentative strategies between two opposed sides? Analysis showed very weak argumentation and frequent use of appeals to emotions, especially appeal to fear, for both supporters and opponents to EU.